Elimination of head and neck cancer initiating cells through targeting glucose regulated protein78 signaling - Wu, Meng-Ju; Jan, Chia-Ing; Tsay, Yeou-Guang; Yu, Yau-Hua; Huang, Chih-Yang; Lin, Shu-Chun; Liu, Chung-Ji; Chen, Yu-Syuan; Lo, Jeng-Fan; Yu, Cheng-Chia (Molecular cancer, 2010)
Head and neck squamous cell carcinoma (HNSCC) is a highly lethal cancer that contains cellular and functional heterogeneity. Previously, we enriched a subpopulation of highly tumorigenic head and neck cancer initiating cells (HN-CICs) from HNSCC. However, the molecular mechanisms by which to govern the characteristics of HN-CICs remain unclear. GRP78, a stress-inducible endoplasmic reticulum chaperone, has been reported to play a crucial role in the maintenance of embryonic stem cells, but the role of GRP78 in CICs has not been elucidated. Initially, we recognized GRP78 as a putative candidate on mediating the stemness and tumorigenic properties of HN-CICs by differential systemic analyses. Subsequently, cells with GRP78 anchored at the plasma membrane (memGRP78+) exerted cancer stemness properties of self-renewal, differentiation and radioresistance. Of note, xenotransplantation assay indicated merely 100 memGRP78+ HNSCCs resulted in tumor growth. Moreover, knockdown of GRP78 significantly reduced the self-renewal ability, side population cells and expression of stemness genes, but inversely promoted cell differentiation and apoptosis in HN-CICs. Targeting GRP78 also lessened tumorigenicity of HN-CICs both in vitro and in vivo. Clinically, co-expression of GRP78 and Nanog predicted the worse survival prognosis of HNSCC patients by immunohistochemical analyses. Finally, depletion of GRP78 in HN-CICs induced the expression of Bax, Caspase 3, and PTEN. In summary, memGRP78 should be a novel surface marker for isolation of HN-CICs, and targeting GRP78 signaling might be a potential therapeutic strategy for HNSCC through eliminating HN-CICs.